Islamic law in the Indian Ocean world
1 online resource.
Keywords: "This book explores the ways in which Muslim communities across the Indian Ocean world produced and shaped Islamic law and its texts, ideas and practices in their local, regional, imperial, national, and transregional contexts. With a focus on the production and transmission of Islamic law in the Indian Ocean, the chapters in this book draw from and add to recent discourses on the legal histories and legal anthropologies of the Indian Ocean rim as well as to the conversations on global Islamic circulations, legal history and anthropology of the Indian Ocean. By doing so, this book argues for the importance of Islamic legal thoughts and practices of the so-called "peripheries" to the core and kernel of Islamic traditions and the urgency to address their long-existing role in the making of historical and human experience of the religion. Arguing that Islamic law was and is not merely brought to, but also produced in the Indian Ocean world through constant and critical engagements, the book explores the ways in which Muslim communities in the Indian Ocean world shaped and continue to shape their lives and thoughts within the legal frameworks of their religion. The book takes a long historical perspective on Islamic law for a better understanding of the ways in which the oceanic Muslims have historically developed their religious, juridical, and intellectual traditions. Transregional and transdisciplinary in its approach, this book will be of interest to scholars of Islamic Studies, Indian Ocean Studies, Legal History and Legal Anthropology, Area Studies of South and Southeast Asia and East Africa"--